Benchmarking hospital units' efficiency using data envelopment analysis: The case of greek obstetric and gynaecology public units - Katharaki, Maria (Handbook of Optimization Theory: Decision Analysis and Application, 2011)
Hospital institution's managers are called upon to combine and utilize efficiently the finite financial resources toward the goal of maximizing the number and quality of health services offered. The research aim of this study is to primarily estimate the relative technical efficiency by using a sample from public hospital units that provide obstetrical and gynaecological services in Greece and secondly, to emphasize the policy implications for health sector policy-makers. In order to effectively address the above goals, a comparative analysis of 32 Greek Public Hospital Units was conducted. The research was based on data collected from official public sources. Quantitative analysis, specifically data envelopment analysis (DEA) is used to estimate efficiency of hospital units. Based on the results that emerge from the application of Data Envelopment Analysis, information is provided to their managers, which refer to: (i) the degree of utilization of their production factors, (ii) the particular weight of each production factor in the modulation of the relative technical efficiency score, (iii) the utilization level of each production factor, and (iv) those hospital units that utilize their resources in an optimal way and constitute models for the exercising of effective management. Particular emphasis is given to the economic efficiency of central region hospital units' relative to those of the outlying regions. The derived information assists in the modulation of an appropriate policy mix per hospital unit which should be applied by their management teams along with a set of administrative measures that need to be undertaken in order to promote efficiency. © 2011 by Nova Science Publishers, Inc. All rights reserved.